1971
DOI: 10.2136/sssaj1971.03615995003500010041x
|View full text |Cite
|
Sign up to set email alerts
|

Role of Humic Carrier Substances in DDT Movement through Forest Soil

Abstract: In DDT-treated forest floor columns, over 30 times as much DDT was recovered by leaching with water when urea was added to disperse the humic acids. Using similar treatment and analysis, alundum tension lysimeters in soil 2 cm below the forest floor yielded no detectable levels of DDT. In DDTtreated humic extracts, 91% of added o,p'-DDT was recovered in humic acids and 9% in fulvic acids plus water.Additional Key Words for Indexing: DDT, forest humus, humic acid, lysimetry.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
34
0

Year Published

1985
1985
2012
2012

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(35 citation statements)
references
References 0 publications
1
34
0
Order By: Relevance
“…The earliest studies on colloid-facilitated transport focused on the mobility of hydrophobic pesticides and herbicides. The presence of natural organic matter (NOM), such as humic and fulvic acids, increased the solubility and mobility of DDT, phenanthrene, naphthalene, and napropamide (Kan and Tomson 1990, McDowell-Boyer et al 1986, Means and Wijayarante 1982, Ballard 1971. McCarthy and Jimenez (1985) found that there was a direct relationship between the chemical hydrophobicity and its affinity for humic acids.…”
Section: Non-radioactive Contaminant Transport With Colloidsmentioning
confidence: 99%
“…The earliest studies on colloid-facilitated transport focused on the mobility of hydrophobic pesticides and herbicides. The presence of natural organic matter (NOM), such as humic and fulvic acids, increased the solubility and mobility of DDT, phenanthrene, naphthalene, and napropamide (Kan and Tomson 1990, McDowell-Boyer et al 1986, Means and Wijayarante 1982, Ballard 1971. McCarthy and Jimenez (1985) found that there was a direct relationship between the chemical hydrophobicity and its affinity for humic acids.…”
Section: Non-radioactive Contaminant Transport With Colloidsmentioning
confidence: 99%
“…The association of many organic pollutants including DDT (Ballard 1971;Pierce et al 1974;Carter & Suffet 1982;Chiou et al 1986;Lee & Farmer 1989), with humic material is well documented. Much of this work has focused on the increase in solubility that results from the association of DDT with the soluble humic fractions.…”
Section: Weakly Bound Residuesmentioning
confidence: 99%
“…They are divided into humic acids (which are acidprecipitated from basic soil extracts), fulvic acids (which are soluble in both acid and base), and the insoluble humin fraction. Ballard (1971) examined the amount of DDT that leached from samples of a forest soil freshly treated with DDT. Leaching was low unless the soil was treated with urea, and then substantial DDT recovery was obtained.…”
Section: Weakly Bound Residuesmentioning
confidence: 99%
See 1 more Smart Citation
“…Naturally occurring organic matter is present in both particulate and dissolved states. Whill~ the interaction between hydrophobic compounds and dissolved organic matter is poorly understood, chlorinated hydrocarbons in aqueous systems have been shown to associate strongly with the organic matter of soils (37,(61)(62)(63)(64)(65)(66)(67)(68)(69)(70)(71), sediments (37,(71)(72)(73),…”
Section: Introductionmentioning
confidence: 99%